A Subannual Subsurface Pathway From the Gulf Stream to the Subpolar Gyre and Its Role in Warming and Salinification in the 1990s. Issue 13 (6th July 2019) - Jacobs, Zoe L.; Grist, Jeremy P.; Marsh, Robert; Josey, Simon A.
Abstract: The transport of warm, saline subtropical water to the subpolar gyre (SPG) in the North Atlantic has been the subject of a range of Lagrangian studies, establishing intergyre exchange on timescales of 2–7 years, with greater subsurface throughflow. Here calculating particle trajectories in a high‐resolution, global hindcast, we present new evidence for a direct, subsurface pathway to the SPG from the Gulf Stream (GS) on subannual timescales. The pathway is most evident for particles initially at 200‐m depth in the GS and is enhanced after a prolonged period of positive North Atlantic Oscillation. This occurred in the mid‐1990s and led to warming and salinification of the western SPG consistent with observations. The more realistic advective pathways and timescales in the high‐resolution model enable, for the first time, attribution of temperature and salinity changes in the SPG to a direct influx of GS water. Plain Language Summary: The downstream destination of Gulf Stream water is investigated using a technique that tracks water parcels with a state‐of‐the‐art ocean model. This approach allows us to obtain new evidence for a fast pathway by which water starting in the Florida Straits at the subsurface (at about 200 m deep) can reach the subpolar North Atlantic on timescales as short as 4 months. Surface waters were more likely to be recirculated within the subtropical region. The subsurface pathway was found to be enhanced during the 1990s, which led to increased temperature and salinity in the western subpolar North Atlantic, in agreement with observations made at this time. Our results have physical and biological implications and indicate that the connection between the subtropical and subpolar North Atlantic on subannual timescales is a key element of the Atlantic climate system. Key Points: Rapid (<1 year) subsurface pathway from Gulf Stream to subpolar gyre is identified for the first time using targeted particle tracking Pathway is most evident for particles initially at 200‐m depth and is enhanced after a positive phase of the North Atlantic Oscillation Western subpolar gyre warming and salinification since the 1990s attributed to anomalous advection via the new pathway